2017
DOI: 10.21059/buletinpeternak.v41i2.13376
|View full text |Cite
|
Sign up to set email alerts
|

Autentikasi Daging Ayam Segar Dari Kontaminasi Daging Babi Menggunakan Gen Cyt-B Dengan Analisis Duplex- Polymerase Chain Reaction

Abstract: Halal is one of important aspects in consumer protection. Meat and processed meat products are food that should be controlled strictly because those are prone to be adulterated by pork contamination. Therefore, it is necessary to provide detection technique which is accurate, fast and cheap. The objective of this research was to identify the presence of impurities of pork meat on raw chicken meat using gene Cyt-b with duplex-PCR analysis. This research used six samples of raw chicken meat and raw pork. Raw chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…This analysis performed to ensure that oligonucleotide primers designed in this study and other components of PCR were working together and they could be used as a marker for identification of dog and rat in food products containing beef and bovine derivatives. The studies in food authentication using PCR technology were reported using duplex PCR mitochondrial Cytochrome b gene to detect pork and chicken contamination in raw meats and meatballs using published primers (Ni'mah et al, 2016;Hertanto et al, 2017;Novianty et al, 2017). The use of mitochondrial 12S rRNA gene as a marker for species identification had been successfully conducted using sequence analysis of processed meats samples.…”
Section: Species Identification Using Multiplex Pcr 12s Rrna Genementioning
confidence: 99%
See 2 more Smart Citations
“…This analysis performed to ensure that oligonucleotide primers designed in this study and other components of PCR were working together and they could be used as a marker for identification of dog and rat in food products containing beef and bovine derivatives. The studies in food authentication using PCR technology were reported using duplex PCR mitochondrial Cytochrome b gene to detect pork and chicken contamination in raw meats and meatballs using published primers (Ni'mah et al, 2016;Hertanto et al, 2017;Novianty et al, 2017). The use of mitochondrial 12S rRNA gene as a marker for species identification had been successfully conducted using sequence analysis of processed meats samples.…”
Section: Species Identification Using Multiplex Pcr 12s Rrna Genementioning
confidence: 99%
“…Meats adulteration is prohibited due to violation of consumer rights and rule of food safety, therefore, the effort to identify meat adulteration accurately is needed (Mahajan et al, 2010). In addition, Hertanto et al (2017) reported that contamination undesired species in meat products do not only happen intentionally but also accidentally. By using same meat grinder for different species without strict control will automatically contaminate meat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keanekaragaman sifat dan ciri yang dimiliki trenggiling (Manis javanica Desmarest, 1822), menggambarkan potensi dan manfaat, diantara-nya adalah daging dan sisiknya yang diyakini sebagai obat dan makanan (Zainuddin, 2008;Hertanto, 2010). Menyadari akan keanekaragaman potensi, manfaat, dan nilai ekonomi yang dimiliki trenggiling, maka perlu dilakukan penelitian di penangkaran untuk memperoleh pengetahuan dan teknologi yang mendukung pelestarian serta pemanfaatannya secara tepat.…”
Section: Trenggilingunclassified